Management of technology : key success factors for innovation and sustainable development : selected papers from the twelfth International Conference on Management of Technology - Morel-Guimaraes, Laure; Hosni, Yasser A.; Khalil, Tarek M. (Elsevier, 2005)
The 12th International Conference of the International Association for Management of Technology (IAMOT) held in March 2002 in Nancy, France, focused on "Innovation and Sustainable Development". These conferences present a unique opportunity to exchange best practice while debating new concepts of managing innovation, technology and R & D. IAMOT remains a major scientific forum where leading researchers and practitioners meet. This book represents a selection of the best contributions presented in Nancy.